Determinants of voter behaviour at presidential elections in a post-socialist context - Hafner-Fink, Mitja (Družboslovne razprave, 2014)
This article attempts to fill the gap in the literature regarding the determinants of voter behaviour at presidential elections in a post-socialist context, taking into account the changing patterns of competition both within the party system (parliamentary elections) and at presidential elections. Slovenia is taken as a case study of predictors of voting behaviour at presidential elections (1997, 2002, 2007 and 2012) based on bivariate and multivariate methods using Politbarometer public opinion survey data. The key findings are that the predictors of voting behaviour change over time and that party identification has recently been declining in importance as a predictor of voting behaviour at presidential elections.
Keywords: Predsedniške volitve; Presidential elections; Volilci; Voters; Case studies; Študije primerov; Slovenia; Slovenija; javno mnenje